Association between gastrointestinal diseases and osteoarthritis risk based on data from NHANES 2011–2018 - Mingzhu Lu; Yangkun Ding (PLoS ONE, 2025)
Osteoarthritis (OA) and gastrointestinal diseases are two significant public health problems. However, the association between the two is unclear. This study aimed to investigate the biological relationship between gastrointestinal diseases and OA using data derived from the National Health and Nutrition Examination Survey (NHANES) database. A total of 8,833 participants registered in the NHANES between 2011 and 2018 were enrolled; 5,044 participants were included in the study after excluding ineligible samples. Three models were constructed to investigate the correlation between gastrointestinal diseases and OA. Risk stratification analysis was conducted, and a receiver operating characteristic (ROC) curve was employed. Among 5,044 participants, even after stratification, gastrointestinal diseases significantly affected OA occurrence; this effect persisted despite adjusting for all covariates in model 3 (odds ratio = 2.01; 95% confidence interval = 1.23–3.3, p = 0.0069) and was confirmed by risk-stratification analysis. The ROC curve and the smooth curve showed that gastrointestinal diseases increased OA risk. Gastrointestinal diseases are significant risk factors for OA, which indicates a potential theoretical basis for OA prevention.